Photomorphogenic and thermomorphogenic responses influencing growth and flowering in Chrysanthemum morifolium cv. Zembla - SANGMESH, PANCHAL; SINGH, MAM CHAND; KUMAR, GUNJEET; NAMITA; SATHEE, LEKSHMY; KUMAR, AMRENDER; SINGH, LOKENDRA; AMALA, EDIGA; SHREEKANT (The Indian Journal of Agricultural Sciences, 2025)
Light and temperature act as key environmental signals that synergistically influence plant growth and development. Strategically manipulating photothermal regimes offers remarkable potential to optimize plant architecture and flowering. The study was carried out during 2023–24 and 2024–25 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the photomorphogenic and thermomorphogenic responses in Chrysanthemum morifolium cv. Zembla. Plants were subjected to different monochromatic light treatments (W, R, B, RB, and FL) under 15 h of long-day photoperiod across five temperature regimes (24/20°C, 22/2°C, 20/20°C, 18/20°C, and 16/20°C). The research revealed significantly distinctive responses across different morphophysiological and flowering parameters. Morphological results revealed that red light (R, LD15) at 24/20°C significantly increased plant height (92.97 cm) and internodal length (2.73 cm), while, blue light (B, LD15) at 24/20°C enhanced vegetative growth, attributed by maximum leaf number (35.82), leaf area (379.87 cm²), total plant dry weight (10.80 g), and enhanced physiological mechanisms including relative growth rate (0.046 g/g/day) and crop growth rate (2.030 g/m²/day). For flowering responses, blue light accelerated bud induction across all temperatures, with plants under B, LD15 achieving anthesis earlier than alternative spectral treatments. Sub-optimal temperature (16/20°C) under blue light accelerated the induction of visible bud formation and flowering, whereas optimal temperature conditions (24/20°C) under blue light resulted in superior capitulum development characterized by maximum floral diameter (9.97 cm). The synergistic interaction between light and temperature proved to effective for modulating chrysanthemum growth and development, providing valuable insights for optimizing environmentally controlled cultivation practices.